Food system transformation and diet quality among a rising middle class in Mozambique - Smart, Jenny; Tschirley, David; Smart, Francis C. (Agricultural and Applied Economics Association, 2019)
The overweight and obesity epidemic is on the rise globally among developed nations, as it is also quickly evolving among the rapidly expanding middle class in developing nations such as those in sub‐Saharan Africa (SSA); As incomes rise, households increasingly purchase more perishable foods such as meats, dairy, fruits and vegetables, as well as processed foods, many of which are which are of little nutritional worth; Meanwhile, the rural population continues to grow in SSA and in Mozambique, like in other countries, migration by those exiting farming life to pursue jobs in a nearby urban center is leading to a proliferation of rapidly expanding towns and cities across the country; For some, it is possible to continue farming a plot of land, even from within a town or city, to help supply personal food consumption; No one has analytically showed relationship between own farming, city size, and nutritional outcomes.